Combination of in silico and cell culture strategies to predict biomaterial performance: Effects of sintering temperature on the biological properties of hydroxyapatite - de Almeida, Gerson S. [UNESP]; Ferreira, Marcel R. [UNESP]; Fernandes, Célio C. [UNESP]; de Biagi, Carlos A. O.; Silva, Wilson Araújo; Rangel, Elidiane C. [UNESP]; Lisboa-Filho, Paulo N. [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2024)
Advances in methodologies to evaluate biomaterials brought an explosive growth of data, ensuing computational challenges to better analyzing them and allowing for high-throughput profiling of biological systems cost-efficiently. In this sense, we have applied bioinformatics tools to better understand the biological effect of different sintering temperatures of hydroxyapatite (abbreviated HA; at 1100, 1150, and 1250°C) on osteoblast performance. To do, we have better analyzed an earlier deposited study, in which the access code is E-MTAB-7219, which the authors have explored different in silico tools on this purpose. In this study, differential gene expression analyses were performed using the gene set variation analysis (GSVA) algorithm from the transcriptomes respecting the thermal changes of HA, which were validated using exclusively in vitro strategies. Furthermore, in silico approaches elected biomarkers during cell behavior in response to different sintering temperatures of HA, and it was further validated using cell culture and qPCR technologies. Altogether, the combination of those strategies shows the capacity of sintered HA at 1250°C to present a better performance in organizing an adequate microenvironment favoring bone regeneration, angiogenesis and material resorption stimulus once it has promoted higher involvement of genes such as CDK2, CDK4 (biomarkers of cell proliferation), p15, Osterix gene (related with osteogenic differentiation), RANKL (related with osteoclastogenesis), VEGF gene (related with angiogenesis), and HIF1α (related with hypoxia microenvironment). Altogether, the combination of in silico and cell culture strategies shows the capacity of sintered HA at 1250°C in guaranteeing osteoblast differentiation and it can be related in organizing an adequate microenvironment favoring bone regeneration, angiogenesis, and material resorption stimulus.
Keywords: bioengineering; bioinformatics; biomaterial; hydroxyapatite; osteoblast; tissue regeneration